The aesthetic features of using Raku in ceramics Uta Grossmann Objects: غيد صادق عبد الغني (Al-Academy, 2016)
The Ceramic was a part from the humanitarian production that masseure the development and promotion of the Nations through decades. The Ceramic development involve wide and more techniques. One of these techniques that appear through the developmental centuries, the ( Alkaro Ceramic )technique, this technique depended the simplicity that comitted on religions thoughts through their development and its origin, so it had connected with these religions thoughts and had transmitted to the differnt Nations and they development in it to stay as a connection to the original key although its a way to keep them from adoption a new path. The tracker of the Ceramic fine art through its modernal level could knew and touched the Enormons transformation in Asthetic Values and Visions. Ceramic is apole of neumorous variations of arts that left not only the old styles but also the modern too for the benfit of the modernal fine art culture. According to this research, the Researcher wants to focus on a very special techniques of Alrako Ceramic by a german Ceramiacian ( Uta Grossmann ) and shows us how she ( Uta Grossmann ) analies her product to declear its privacy Contain in special. This german Ceramician is considered, one of the most famous modern Ceramician. The Critics and Art Professionals in Arts consider her as one of the most important, famous Ceramician in modernal fine Art in germany as well as in all Europe. Back to her references and their effects in modernal Ceramic fine Art, man can notice that she has privacy especially she belongs to a nation witch has tradition and at the same time has contacts with the other nations which lead to the modernal Ceramic fine Art development